2015
DOI: 10.1007/s00418-015-1307-5
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of skeletal muscle Ankrd2 protein in human cardiac tissue and neonatal rat cardiomyocytes

Abstract: Muscle-specific mechanosensors Ankrd2/Arpp (ankyrin repeat protein 2) and Ankrd1/CARP (cardiac ankyrin repeat protein) have an important role in transcriptional regulation, myofibrillar assembly, cardiogenesis and myogenesis. In skeletal muscle myofibrils, Ankrd2 has a structural role as a component of a titin associated stretch-sensing complex, while in the nucleus it exerts regulatory function as transcriptional co-factor. It is also involved in myogenic differentiation and coordination of myoblast prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 57 publications
1
8
0
1
Order By: Relevance
“…1e ). ID association for both proteins was recently also described by Jasnic-Savovic and colleagues 35 . Consistent with a previously reported interaction between CARP1 and phospholipase-C (PLC) 36 , we demonstrated in pull-down assays that the coiled coil region of PLCβ1, the main PLC isoform in hearts 37 , binds to both CARP1 and CARP2 ( Fig.…”
Section: Resultssupporting
confidence: 55%
“…1e ). ID association for both proteins was recently also described by Jasnic-Savovic and colleagues 35 . Consistent with a previously reported interaction between CARP1 and phospholipase-C (PLC) 36 , we demonstrated in pull-down assays that the coiled coil region of PLCβ1, the main PLC isoform in hearts 37 , binds to both CARP1 and CARP2 ( Fig.…”
Section: Resultssupporting
confidence: 55%
“…Studies on the localization of ANKRD1 have yielded differing results. Jasnic-Savovic et al 27 demonstrated a strong positive immunoreaction for ANKRD1 in the cytoplasm, which coincided with striation of the sarcomere, although ANKRD1 was not detected in the nucleus. The absence of ANKRD1 in the nucleus was confirmed by Ishiguro et al 28 However, Zou et al 11 found ANKRD1 expression in the nuclei of rodent cultured cardiac cells, and several studies have demonstrated that ANKRD1 has a dual subcellular localization, where FIGURE 4 P.S187F mutation modulates the localization of exogenous ANKRD1 in HEK293 cells.…”
Section: Discussionmentioning
confidence: 95%
“…Studies on the localization of ANKRD1 have yielded differing results. Jasnic‐Savovic et al . demonstrated a strong positive immunoreaction for ANKRD1 in the cytoplasm, which coincided with striation of the sarcomere, although ANKRD1 was not detected in the nucleus.…”
Section: Discussionmentioning
confidence: 98%
“…Expression of MARPs in adult mammalian skeletal muscle and the heart is well documented [ 3 – 5 , 59 , 63 ]. In humans, ANKRD1 and ANKRD2 were detected mostly in the heart and skeletal muscles, respectively.…”
Section: Discussionmentioning
confidence: 99%